Toward an Organismal Neurobiology: Integrative Neuroethology - Satterlie, Richard A. (Oxford University Press, 2013)
Overt behavior is generated in response to a palette of external and internal stimuli and internal drives. Rarely are these variables introduced in isolation. This creates challenges for the organism to sort inputs that frequently favor conflicting behaviors. Under these conditions, the nervous system relies on established and flexible hierarchies to produce appropriate behavioral changes. The pteropod mollusc Clione limacina is used as an example to illustrate a variety of behavioral interactions that alter a baseline behavioral activity: slow swimming. The alterations include acceleration within the slow swimming mode, acceleration from the slow to fast swimming modes, whole body withdrawal (and inhibition of swimming), food acquisition behavior (with a feeding motivational state), and a startle locomotory response. These examples highlight different types of interaction between the baseline behavior and the new behaviors that involve external stimuli and two types of internal drives: a modular arousal system and a motivational state. The investigation of hierarchical interactions between behavioral modules is a central theme of integrative neuroethology that focuses on an organismal level of understanding of the neural control of behavior.